The persistence of female circumcision in Nigeria: a case study of the Okpe people of Delta State (1994)
The paper attempted to examine the reasons accounting for the sustenance of the practice of female circumcision and how to stem it. The basis of the facts presented here are derived from a survey involving a sample of four hundred and five respondents of both sexes conducted in two local government areas (Okpe and Sapele) of Delta state. The subjects that constituted the sample were randomly chosen and the data analysed through simple descriptive and inferential statistics. The results showed that the persistence of female circumcision is due to the application of western methods in the operation thereby reducing the agony and stress associated with the practice. It also identified the low level of education and urbanisation as factors inducing the sustainability of the practice because they make for the persistence of traditional norms and values. Consequent upon these findings, the paper concluded by suggesting the involvement and enlistment of western trained health care professionals as public health educator in an attempt to stamp out the act. In addition to the above, the paper suggested the rapid development of our educational system and urbanisation as a way of weakening non functional traditional values.